2016
DOI: 10.1080/01904167.2016.1262415
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in nutrient uptake and nutrient use efficiency of oil palm

Abstract: Observations of the vegetative and reproductive biomass produced annually and the mineral element contents have been conducted on diverse oil palm plant materials tested in a genetic test in Indonesia. The results show that the nutrient uptake (for trunk growth, leaf renewal and bunch export) greatly varies (CV = 10% for N uptake and 17% for K uptake) with the origins of the planting materials considered. For equivalent production, the uptake in nutrients of certain plant material may differ very significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…Indeed, differences in susceptibility have been found between progenies and between clones for different minerals (Cochard et al, 2005;Ollivier et al, 2016). However, whether those differences in behaviour reflect different needs remains to be demonstrated.…”
Section: Breeding For Improved Mineral Nutrition Under Climate Changementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, differences in susceptibility have been found between progenies and between clones for different minerals (Cochard et al, 2005;Ollivier et al, 2016). However, whether those differences in behaviour reflect different needs remains to be demonstrated.…”
Section: Breeding For Improved Mineral Nutrition Under Climate Changementioning
confidence: 99%
“…Also, a strong challenge will be to successfully plant oil palm in areas that will not be the most favourable any more while preserving regions harbouring valuable biodiversity. Under Genotype  Environment trials, the Genetics  Mineral Nutrition interaction is being considered (Ollivier et al, 2016). Mycorrhizal infection may increase with warmer temperatures, and lower effects of N and P limitation in nutrient-poor soils (adapted from Pilbeam, 2015).…”
Section: Breeding For Improved Mineral Nutrition Under Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…In order to reach such high productivity, nutrient such as N, P, K, Mg, and B are needed in most soil (Ng, 1997). Deficiency of this nutrient can lower the production (Woittiez et al, 2017), but nutrient criteria and end production depend on the type of soils (Goh, 2005) and plants necessity (Ollivier et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Another important finding from Ollivier et al [114] demonstrated that the oil palm plant nutrient levels are genotypedependent. According to their study, under the same growing conditions and with a similar fertilizer regime, planting materials were significantly different in most of the nutrient concentrations of the organs observed.…”
Section: Oil Palm Omics Research Related To Yieldmentioning
confidence: 99%